# RD Sharma Solutions Class 7 Chapter 7 Algebraic Expressions

Read RD Sharma Solutions Class 7 Chapter 7 Algebraic Expressions below, students should study RD Sharma class 7 Mathematics available on Studiestoday.com with solved questions and answers. These chapter wise answers for class 7 Mathematics have been prepared by teacher of Grade 7. These RD Sharma class 7 Solutions have been designed as per the latest NCERT syllabus for class 7 and if practiced thoroughly can help you to score good marks in standard 7 Mathematics class tests and examinations

Exercise 7.1

Question 1: Identify the monomials, binomials, trinomials and quadrinomials from the following expressions:

(i) a2

(ii) a2 − b2

(iii) x3 + y3 + z3

(iv) x+ y+ z3 + 3xyz

(v) 7 + 5

(vi) a b c + 1

(vii) 3x – 2 + 5

(viii) 2x – 3y + 4

(ix) x y + y z + z x

(x) ax3 + bx2 + cx + d

Solution 1:

(i) a2

a2 contains only one term. That is why it is a monomial expression.

(ii) a2 − b2

a− b2 contains two terms. That is why it is a binomial expression.

(iii) x3 + y3 + z3

x3 + y3 + z3 contains three terms. That is why it is a trinomial expression.

(iv) x+ y+ z3 + 3xyz

x3 + y+ z3 + 3xyz contains four terms. That is why it is a quadrinomial expression.

(v) 7 + 5

7 + 5 = 12 contains one terms. That is why it is a monomial expression.

(vi) a b c + 1

a b c + 1 contains two terms That is why it is a binomial expression.

(vii) 3x – 2 + 5

3x – 2 + 5 contains two terms That is why it is a binomial expression.

(viii) 2x – 3y + 4

2x – 3y + 4 contains three terms That is why it is a trinomial expression.

(ix) x y + y z + z x

x y + y z + z x contains three terms is a trinomial expression.

(x) ax3 + bx2 + cx + d

ax3 + bx2 + cx + d contains four terms That is why it is a quadrinomial expression.

Question 2: Write all the terms of each of the following algebraic expressions:

(i) 3x

(ii) 2x – 3

(iii) 2x2 − 7

(iv) 2x+ y− 3xy + 4

Solution 2:

(i) 3x = is the only term of the given algebraic expression.

(ii) 2x – 3 = 2x and -3 are the terms of the given algebraic expression.

(iii) 2x2 – 7 = 2x2 and −7 are the terms of the given algebraic expression.

(iv) 2x+ y− 3xy + 4 = 2x2, y2, −3xy and 4 are the terms of the given algebraic expression.

Question 3: Identify the terms and also mention the numerical coefficients of those terms:

(i) 4xy, -5x2y, -3yx, 2xy2

(ii) 7a2bc,-3ca2b,  (-5/2)abc2, (3/2)abc2, (-4/3)cba2

Solution 3:

(i) Like terms 4xy, -3yx and Numerical coefficients of these are 4, -3

(ii) Like terms (7a2bc, −3ca2b) and (-4/3)cba2 and their Numerical coefficients are 7, -3,(-4/3)

Like terms are  (-5/2)abc2 and (3/2)abc2 and their numerical coefficients are (-5/2)  and (3/2)

Question 4: Identify the like terms in the following algebraic expressions:

(i) a2 + b-2a2 + c2 + 4a

(ii) 3x + 4xy − 2yz + 52zy

(iii) abc + ab2c + 2acb+ 3c2ab + b2ac − 2a2bc + 3cab2

Solution 4:

(i) a2 + b-2a2 + c2 + 4a

The like terms in the a2 + b-2a2 + c2 + 4a algebraic expressions are a2 and −2a2.

(ii) 3x + 4xy − 2yz + 52zy

The like terms in the 3x + 4xy − 2yz + 52zy algebraic expressions are -2yz and 52zy.

(iii) abc + ab2c + 2acb+ 3c2ab + b2ac − 2a2bc + 3cab2

The like terms in the abc + ab2c + 2acb+ 3c2ab + b2ac − 2a2bc + 3cab2 algebraic expressions are ab2c, 2acb2, b2ac and 3cab2.

Question 5: Write the coefficient of x in the following:

(i) –12x

(ii) –7xy

(iii) xyz

(iv) –7ax

Solution 5:

(i) -12x = numerical coefficient of x is -12.

(ii) -7xy = numerical coefficient of x is -7y.

(iii) xyz = numerical coefficient of x is yz.

(iv) -7ax = numerical coefficient of x is -7a.

Question 6: Write the coefficient of x2 in the following:

(i) −3x2

(ii) 5x2yz

(iii) 5/7 x2z

(iv)  (-3/2)ax2 + yx

Solution 6:

(i) −3x2 = numerical coefficient of x2 is -3.

(ii) 5x2yz = numerical coefficient of x2 is 5yz.

(iii) 5/7 x2z = numerical coefficient of x2 is 5/7 z.

(iv)  (-3/2)ax2 + yx = numerical coefficient of x2 is  (-3/2)a.

Question :7. Write the coefficient of:

(i) y in –3y

(ii) a in 2ab

(iii) z in –7xyz

(iv) p in –3pqr

(v) y2 in 9xy2z

(vi) x3 in x3 +1

(vii) x2 in − x2

Solution 7:

(i) –3y = coefficient of y is -3.

(ii) 2ab = coefficient of a is 2b.

(iii) -7xyz = coefficient of z is -7xy.

(iv) -3pqr = The coefficient of p is -3qr.

(v) 9xy2z = coefficient of y2 is 9xz.

(vi) x3 +1 = coefficient of x3 is 1.

(vii) − x2 = coefficient of x2 is -1.

Question 8: Write the numerical coefficient of each in the following:

(i) xy

(ii) -6yz

(iii) 7abc

(iv) -2x3y2z

Solution 8:

(i) xy = numerical coefficient in the term xy is 1.

(ii) -6yz = numerical coefficient in the term – 6yz is – 6.

(iii) 7abc = numerical coefficient in the term 7abc is 7.

(iv)  -2x3y2z = numerical coefficient in the term −2x3y2z is -2.

Question 10: Write the constant term of each of the following algebraic expressions:

(i) x2y − xy2 + 7xy − 3

(ii) a3 − 3a2 + 7a + 5

Solution 10:

(i) x2y − xy2 + 7xy − 3

-3 is the constant term.

(ii) Given a3 − 3a2 + 7a + 5

5 is the constant term.

Question 11: Evaluate each of the following expressions for x = -2, y = -1, z = 3:

(i) (x/y) + (y/z) + (z/x)

(ii) x2 + y2 + z2 – xy – yz – zx

Solution 11:

(i) x = -2, y = -1, z = 3

We take it as: (x/y) + (y/z) + (z/x)

On putting the given values we get,

= ((-2)/(-1)) + ((-1)/3) + (3/(-2))

The LCM of 3 and 2 is 6

= (((12-2-9))/6) = (1/6)

(ii) x = -2, y = -1, z = 3

We take it as: x2 + y2 + z2 – xy – yz – zx

On putting the given values we get,

= (-2)2 + (-1)2 + 32 – (-2) (-1) – (-1) (3) – (3) (-2)

= 4 + 1 + 9 – 2 + 3 + 6

= 23 – 2 = 21

Question 12: Evaluate each of the following algebraic expressions for x = 1, y = -1, z = 2, a = -2, b = 1, c = -2:

(i) ax + by + cz

(ii) ax2 + by2 – cz

(iii) axy + byz + cxy

Solution 12:

(i) x = 1, y = -1, z = 2, a = -2, b = 1, c = -2

We take it as: ax + by + cz

On putting the given values

= (-2) (1) + (1) (-1) + (-2) (2)

= –2 – 1 – 4 = –7

(ii) x = 1, y = -1, z = 2, a = -2, b = 1, c = -2

We take it as: ax2 + by2 – cz

On putting the given values

= (-2) × 12 + 1 × (-1)2 – (-2) × 2

= -2 + 1 – (-4)

= -1 + 4

= 3

(iii) x = 1, y = -1, z = 2, a = -2, b = 1, c = -2

We take it as: axy + byz + cxy

= (-2) × 1 × -1 + 1 × -1 × 2 + (-2) × 1 × (-1)

= 2 + (-2) + 2

= 4 – 2

= 2

Exercise 7.2

(i) 3x and 7x

(ii) -5xy and 9xy

Solution 1:

(i) 3x and 7x

= 3x + 7x

= (3 + 7) x

= 10x

(ii) -5xy and 9xy

= -5xy + 9xy

= (-5 + 9) xy

= 4xy

Question 2: Simplify each of the following:

(i) 7x3y +9yx3

(ii) 12a2b + 3ba2

Solution 2:

(i) 7x3y +9yx3

= (7 + 9) x3y

= 16x3

(ii) 12a2b + 3ba

= (12 + 3) a2b

= 15a2b

(i) 7abc, -5abc, 9abc, -8abc

(ii) 2x2y, – 4x2y, 6x2y, -5x2y

Solution 3:

(i) 7abc, -5abc, 9abc, -8abc

= 7abc + (-5abc) + (9abc) + (-8abc)

= 7abc – 5abc + 9abc – 8abc

= (7 – 5 + 9 – 8) abc [abc taking common]

= (16 – 13) abc

= 3abc

(ii) 2x2y, – 4x2y, 6x2y, -5x2y

= 2x2y +(-4x2y) + (6x2y) + (-5x2y)

= 2x2y – 4x2y + 6x2y – 5x2y

= (2- 4 + 6 – 5) x2y [by taking x2 y common]

= (8 – 9) x2y

= -x2y

Question 4: Add the following expressions:

(i) x3 -2x2y + 3xy2– y3, 2x3– 5xy2 + 3x2y – 4y3

(ii) a4 – 2a3b + 3ab3 + 4a2b+ 3b4, – 2a4 – 5ab3 + 7a3b – 6a2b+ b4

Solution 4:

(i) x3 -2x2y + 3xy2– y3, 2x3– 5xy2 + 3x2y – 4y3

Taking like terms together,

= x3 +2x– 2x2y + 3x2y + 3xy2 – 5xy2 – y3– 4y3

= 3x3 + x2y – 2xy– 5y3

(ii) a4 – 2a3b + 3ab3 + 4a2b+ 3b4, – 2a4 – 5ab3 + 7a3b – 6a2b+ b4

Taking like terms together,

= a4 – 2a4– 2a3b + 7a3b + 3ab3 – 5ab3 + 4a2b2 – 6a2b+ 3b4 + b4

= – a+ 5a3b – 2ab3 – 2a2b+ 4b4

Question 5: Add the following expressions:

(i) 8a – 6ab + 5b, –6a – ab – 8b and –4a + 2ab + 3b

(ii) 5x3 + 7 + 6x – 5x2, 2x2 – 8 – 9x, 4x – 2x2 + 3 x 3, 3 x 3 – 9x – x2 and x – x2 – x3 – 4

Solution 5:

(i) 8a – 6ab + 5b, –6a – ab – 8b and –4a + 2ab + 3b

= (8a – 6ab + 5b) + (–6a – ab – 8b) + (–4a + 2ab + 3b)

Taking positive and negative like terms together,= 8a – 6a – 4a – 6ab – ab + 2ab + 5b – 8b + 3b

= 8a – 10a – 7ab + 2ab + 8b – 8b

= –2a – 5ab

(ii) 5x3 + 7 + 6x – 5x2, 2x2 – 8 – 9x, 4x – 2x2 + 3 x 3, 3 x 3 – 9x – x2 and x – x2 – x3 – 4

= (5 x 3 + 7+ 6x – 5x2) + (2 x 2 – 8 – 9x) + (4x – 2x2 + 3 x 3) + (3 x 3 – 9x-x2) + (x – x2 – x3 – 4)

Taking positive and negative like terms together,

5x3 + 3x3 + 3x3 – x3 – 5x2 + 2x– 2x2– x2 – x2 + 6x – 9x + 4x – 9x + x + 7 – 8 – 4

= 10x3 – 7x2 – 7x – 5

(i) x – 3y – 2z

5x + 7y – 8z

3x – 2y + 5z

(ii) 4ab – 5bc + 7ca

–3ab + 2bc – 3ca

5ab – 3bc + 4ca

Solution 6:

(i)  x – 3y – 2z, 5x + 7y – 8z and 3x – 2y + 5z

= (x – 3y – 2z) + (5x + 7y – 8z) + (3x – 2y + 5z)

Taking positive and negative like terms together,

= x + 5x + 3x – 3y + 7y – 2y – 2z – 8z + 5z

= 9x – 5y + 7y – 10z + 5z

= 9x + 2y – 5z

(ii) Given 4ab – 5bc + 7ca, –3ab + 2bc – 3ca and 5ab – 3bc + 4ca

= (4ab – 5bc + 7ca) + (–3ab + 2bc – 3ca) + (5ab – 3bc + 4ca)

Taking positive and negative like terms together,

= 4ab – 3ab + 5ab – 5bc + 2bc – 3bc + 7ca – 3ca + 4ca

= 9ab – 3ab – 8bc + 2bc + 11ca – 3ca

= 6ab – 6bc + 8ca

Question 7: Add 2x2 – 3x + 1 to the sum of 3x2 – 2x and 3x + 7.

Solution 7:

2x2 – 3x + 1, 3x2 – 2x and 3x + 7

sum of 3x2 – 2x and 3x + 7

= (3x2 – 2x) + (3x +7)

=3x2 – 2x + 3x + 7

= (3x2 + x + 7)

= 2x– 3x + 1+ (3x+ x + 7)

= 2x+ 3x2 – 3x + x + 1 + 7

= 5x– 2x + 8

Question 8: Add x+ 2xy + y2 to the sum of x2 – 3y2and 2x– y2 + 9.

Solution 8:

x+ 2xy + y2, x2 – 3y2and 2x– y2 + 9.

Firstly, find the sum of x2 – 3y2 and 2x2 – y2 + 9

= (x2 – 3y2) + (2x2 – y2 + 9)

= x2 + 2x2 – 3y2 – y2+ 9

= 3x2 – 4y2 + 9

= (x2 + 2xy + y2) + (3x2 – 4y2 + 9)

= x2 + 3x2 + 2xy + y2 – 4y2 + 9

= 4x2 + 2xy  – 3y2+ 9

Question 9: Add a3+ b3 – 3 to the sum of 2a3 – 3b– 3ab + 7 and -a3 + b3 + 3ab – 9.

Solution 9:

a3+ b3 – 3, 2a3 – 3b– 3ab + 7 and -a3 + b3 + 3ab – 9.

First, find the sum of 2a3 – 3b3– 3ab + 7 and – a3 + b3 + 3ab – 9.

= (2a3 – 3b3– 3ab + 7) + (- a3 + b3 + 3ab – 9)

Taking positive and negative like terms together, we get

= 2a3 – a3– 3b3+ b3 – 3ab + 3ab + 7 – 9

= a3 – 2b3 – 2

= (a3 + b3 – 3) + (a3 – 2b3 – 2).

= a3+ a3+ b3– 2b3 – 3 – 2

= 2a3 – b3 – 5

Question 10: Subtract:

(i) 7a2b from 3a2b

(ii) 4xy from -3xy

Solution 10:

(i) 7a2b from 3a2b

= 3a2b -7a2b

= (3 -7) a2b

= – 4a2

(ii) 4xy from -3xy

= –3xy – 4xy

= –7xy

Question 11:  Subtract:

(i) – 4x from 3y

(ii) – 2x from – 5y

Solution 11:

(i) – 4x from 3y

= (3y) – (–4x)

= 3y + 4x

(ii) – 2x from – 5y

= (-5y) – (–2x)

= –5y + 2x

Question 12: Subtract:

(i) 6x−7x+ 5x − 3 from 4 − 5x + 6x2 − 8x3

(ii) − x−3z from 5x– y + z + 7

(iii) x3 + 2x2y + 6xy2 − y3 from y3−3xy2−4x2y

Solution 12:

(i) 6x−7x+ 5x − 3 and 4 − 5x + 6x2 − 8x3

= (4 – 5x + 6x2 – 8x3) – (6x3 – 7x2 + 5x – 3)

= 4 – 5x + 6x2 – 8x3 – 6x3 + 7x2 – 5x + 3

= – 8x3– 6x3 + 7x2 + 6x2– 5x – 5x + 3 + 4

= – 14x3 + 13x2 – 10x +7

(ii) − x−3z and 5x– y + z + 7

= (5x2 – y + z + 7) – (- x2 – 3z)

= 5x2 – y + z + 7 + x2 + 3z

= 5x2+ x2 – y + z + 3z + 7

= 6x2 – y + 4z + 7

(iii) x3 + 2x2y + 6xy2 − y3 and y3−3xy2−4x2y

= (y3 – 3xy2 – 4x2y) – (x3 + 2x2y + 6xy2 – y3)

= y3 – 3xy2 – 4x2y – x3 – 2x2y – 6xy2 + y3

= y3 + y3– 3xy2– 6xy2– 4x2y – 2x2y – x3

= 2y3– 9xy2 – 6x2y – x3

Question 13: From

(i) p3 – 4 + 3p2, take away 5p2 − 3p3 + p − 6

(ii) 7 + x − x2, take away 9 + x + 3x2 + 7x3

(iii) 1− 5y2, take away y3 + 7y2 + y + 1

(iv) x3 − 5x2 + 3x + 1, take away 6x2 − 4x3 + 5 + 3x

Solution 13:

(i) p3 – 4 + 3p2, take away 5p2 − 3p3 + p − 6

= (p3 – 4 + 3p2) – (5p2 – 3p3 + p – 6)

= p3 – 4 + 3p2 – 5p2 + 3p3 – p + 6

= p3 + 3p3 + 3p2 – 5p2– p – 4+ 6

= 4p3 – 2p2 – p + 2

(ii) 7 + x − x2, take away 9 + x + 3x2 + 7x3

= (7 + x – x2) – (9 + x + 3x2 + 7x3)

= 7 + x – x2 – 9 – x – 3x2 – 7x3

= – 7x3– x2 – 3x2 + 7 – 9

= – 7x3 – 4x2 – 2

(iii) 1− 5y2, take away y3 + 7y2 + y + 1

= (1 – 5y2) – (y3+ 7y2 + y + 1)

= 1 – 5y2 – y3 – 7y2 – y – 1

= – y3– 5y2 – 7y2 – y

= – y3– 12y2 – y

(iv) x3 − 5x2 + 3x + 1, take away 6x2 − 4x3 + 5 + 3x

= (x3 – 5x2 + 3x + 1) – (6x2 – 4x3 + 5 +3x)

= x3 – 5x2 + 3x + 1 – 6x2 + 4x3 – 5 – 3x

= x3+ 4x3 – 5x2 – 6x2 + 1 – 5

= 5x3 – 11x2 – 4

Question 14: From the sum of 3x2 − 5x + 2 and − 5x− 8x + 9 subtract 4x2 − 7x + 9.

Solution 14:

Firstly, Add 3x2 − 5x + 2 and − 5x− 8x + 9

= {(3x2 – 5x + 2) + (- 5x2 – 8x + 9)}

= {3x2 – 5x + 2 – 5x2 – 8x + 9}

= {3x2 – 5x2 – 5x – 8x + 2 + 9}

= {- 2x2 – 13x +11}

Then, subtract the result from 4x2 − 7x + 9.

= – 2x2 – 13x + 11 – 4x2 + 7x – 9

= – 2x2 – 4x2 – 13x + 7x + 11 – 9

= – 6x2 – 6x + 2

Question 15: Subtract the sum of 13x – 4y + 7z and – 6z + 6x + 3y from the sum of 6x – 4y – 4z and   2x + 4y – 7.

Solution 15:

Firstly, find the sum of 13x – 4y + 7z and – 6z + 6x + 3y

So, sum of (13x – 4y + 7z) and (–6z + 6x + 3y)

= (13x – 4y + 7z) + (–6z + 6x + 3y)

= (13x – 4y + 7z – 6z + 6x + 3y)

= (13x + 6x – 4y + 3y + 7z – 6z)

= (19x – y + z)

Now find the sum of (6x – 4y – 4z) and (2x + 4y – 7)

= (6x – 4y – 4z) + (2x + 4y – 7)

= (6x – 4y – 4z + 2x + 4y – 7)

= (6x + 2x – 4z – 7)

= (8x – 4z – 7)

Now, Subtract expression = (8x – 4z – 7) – (19x – y + z)

= 8x – 4z – 7 – 19x + y – z

= 8x – 19x + y – 4z – z – 7

= –11x + y – 5z – 7

Question 16: From the sum of x+ 3y2 − 6xy, 2x2 − y2 + 8xy, y2 + 8 and x2 − 3xy subtract −3x2 + 4y2 – xy + x – y + 3.

Solution 16:

Firstly find the sum of (x2 + 3y2 – 6xy), (2x2 – y2 + 8xy), (y2 + 8) and (x2 – 3xy)

={(x2 + 3y2 – 6xy) + (2x2 – y2 + 8xy) + ( y2 + 8) + (x2 – 3xy)}

={x2 + 3y2 – 6xy + 2x2 – y2 + 8xy + y2 + 8 + x2 – 3xy}

= {x2+ 2x2+ x2 + 3y2– y2 + y2– 6xy + 8xy – 3xy + 8}

= 4x2 + 3y2 – xy + 8

Now, subtract the result from  the −3x2 + 4y2 – xy + x – y + 3.

Therefore, subtract the expression

= (4x2 + 3y2 – xy + 8) – (- 3x2 + 4y2 – xy + x – y + 3)

= 4x2 + 3y2 – xy + 8 + 3x2 – 4y2 + xy – x + y – 3

= 4x2 + 3x2+ 3y2– 4y2– x + y – 3 + 8

= 7x2 – y2– x + y + 5

Question 17: What should be added to xy – 3yz + 4zx to get 4xy – 3zx + 4yz + 7?

Solution 17:

By subtracting xy – 3yz + 4zx from 4xy – 3zx + 4yz + 7,

we get the required expression.

Therefore, subtract expression = (4xy – 3zx + 4yz + 7) – (xy – 3yz + 4zx)

= 4xy – 3zx + 4yz + 7 – xy + 3yz – 4zx

= 4xy – xy – 3zx – 4zx + 4yz + 3yz + 7

= 3xy – 7zx + 7yz + 7

Question 18: What should be subtracted from x2 – xy + y2 – x + y + 3 to obtain −x+ 3y− 4xy + 1?

Solution 18:

Let ‘E’ be the required expression. Then,

x2 – xy + y2– x + y + 3 – E = – x2 + 3y2 – 4xy + 1

Therefore, E = (x2 – xy + y2– x + y + 3) – (- x2 + 3y2 – 4xy + 1)

= x2 – xy + y2– x + y + 3 + x2 – 3y2 + 4xy – 1

Taking positive and negative like terms together, we get

= x2 + x2– xy + 4xy + y2– 3y2 – x + y + 3 – 1

= 2x2+ 3xy- 2y2– x + y + 2

Question 19: How much is x – 2y + 3z greater than 3x + 5y – 7?

Solution 19:

Subtracting x – 2y + 3z from 3x + 5y – 7 to get the required expression,

Required expression = (x – 2y + 3z) – (3x + 5y – 7)

= x – 2y + 3z – 3x – 5y + 7

Taking positive and negative like terms together, we get

= x – 3x – 2y + 5y + 3z + 7

= –2x – 7y + 3z + 7

Question 20: How much is x2 − 2xy + 3yless than 2x2 − 3y2 + xy?

Solution 20:

Subtracting the x2 − 2xy + 3y2  from 2x2 − 3y2 + xy to get the required expression,

Required expression = (2x2 – 3y2 + xy) – (x2 – 2xy + 3y2)

= 2x2 – 3y2 + xy – x2 + 2xy – 3y2

Taking positive and negative like terms together, we get

= 2x2– x2 – 3y2 – 3y2 + xy + 2xy

= x2 – 6y2 + 3xy

Question 21:  How much does a− 3ab + 2bexceed 2a− 7ab + 9b2?

Solution 21:

Subtracting 2a− 7ab + 9bfrom a− 3ab + 2bto the required expression

Required expression = (a2– 3ab + 2b2) – (2a2 – 7ab + 9b2)

= a2– 3ab + 2b2 – 2a2 + 7ab – 9b2

Taking positive and negative like terms together, we get

= a– 2a2 – 3ab + 7ab + 2b2 – 9b2

= – a2 + 4ab – 7b2

Question 22: What must be added to 12x− 4x2 + 3x − 7 to make the sum x3 + 2x− 3x + 2?

Solution 22:

Let ‘E’ be the required expression. Thus,

12x3 – 4x2 + 3x – 7 + E = x3 + 2x2 – 3x + 2

Therefore, E = (x3 + 2x2 – 3x + 2) – (12x3 – 4x2 + 3x – 7)

=  x3 + 2x2 – 3x + 2 – 12x3 + 4x2 – 3x + 7

Taking positive and negative like terms together,

= x3– 12x3+ 2x2 + 4x2 – 3x – 3x + 2 + 7

= – 11x3 + 6x2 – 6x + 9

Question 23: If P = 7x2 + 5xy − 9y2, Q = 4y2 − 3x2 − 6xy and R = −4x2 + xy + 5y2, show that P + Q + R = 0.

Solution 23:

P = 7x2 + 5xy − 9y2, Q = 4y2 − 3x2 − 6xy and R = −4x2 + xy + 5y2

To prove: P + Q + R = 0,

P + Q + R = (7x2 + 5xy – 9y2) + (4y2 – 3x2 – 6xy) + (- 4x2 + xy + 5y2)

= 7x2 + 5xy – 9y2 + 4y2 – 3x2 – 6xy – 4x2 + xy + 5y2

Taking positive and negative like terms together, we get

= 7x2– 3x2 – 4x+ 5xy – 6xy + xy – 9y2 + 4y2 + 5y2

= 7x2– 7x+ 6xy – 6xy  – 9y2 + 9y2

= 0

Question 24:  If P = a2 − b2 + 2ab, Q = a+ 4b2 − 6ab, R = b2 + b, S = a− 4ab and T = −2a2 + b2 – ab + a. Find P + Q + R + S – T.

Solution 24:

P = a2 − b2 + 2ab, Q = a+ 4b2 − 6ab, R = b2 + b, S = a− 4ab and T = −2a2 + b2 – ab + a.

Find P + Q + R + S – T

Substituting all values

= P + Q + R + S – T = {(a2 – b2 + 2ab) + (a2 + 4b2 – 6ab) + (b2 + b) + (a2 – 4ab)} – (-2a2 + b2 – ab + a)

= {a2 – b2 + 2ab + a2 + 4b2 – 6ab + b2 + b + a2 – 4ab}- (- 2a2 + b2 – ab + a)

= {3a2 + 4b2 – 8ab + b } – (-2a2 + b2 – ab + a)

= 3a2+ 4b2 – 8ab + b + 2a2 – b2 + ab – a

positive and negative like terms together, we get

3a2+ 2a2 + 4b2 – b2 – 8ab + ab – a + b

= 5a2 + 3b2– 7ab – a + b

Exercise 7.3

Question 1: Place the last two terms of the following expressions in parentheses preceded by a minus sign:

(i) x + y – 3z + y

(ii) 3x – 2y – 5z – 4

(iii) 3a – 2b + 4c – 5

(iv) 7a + 3b + 2c + 4

(v) 2a– b2 – 3ab + 6

(vi) a2 + b2 – c2 + ab – 3ac

Solution:

(i) x + y – 3z + y

x + y – 3z + y

= x + y – (3z – y)

(ii)  3x – 2y – 5z – 4

3x – 2y – 5z – 4

= 3x – 2y – (5z + 4)

(iii) 3a – 2b + 4c – 5

3a – 2b + 4c – 5

= 3a – 2b – (–4c + 5)

(iv) 7a + 3b + 2c + 4

7a + 3b + 2c + 4

= 7a + 3b – (–2c – 4)

(v) 2a– b2 – 3ab + 6

2a– b2 – 3ab + 6

= 2a2 – b2 – (3ab – 6)

(vi)  a2 + b2 – c2 + ab – 3ac

a2 + b2 – c+ ab – 3ac

= a2 + b2 – c2 – (- ab + 3ac)

Question 2: Write each of the following statements by using appropriate grouping symbols:

(i) The sum of a – b and 3a – 2b + 5 is subtracted from 4a + 2b – 7.

(ii) Three times the sum of 2x + y – [5 – (x – 3y)] and 7x – 4y + 3 is subtracted from 3x – 4y + 7

(iii) The subtraction of x– y2 + 4xy from 2x2 + y2 – 3xy is added to 9x2 – 3y2– xy.

Solution 2:

(i) Sum of a – b and 3a – 2b + 5 = [(a – b) + (3a – 2b + 5)].

By subtracted from 4a + 2b – 7.

Therefore, the required expression is (4a + 2b – 7) – [(a – b) + (3a – 2b + 5)]

(ii) Three times the sum of 2x + y – {5 – (x – 3y)} and 7x – 4y + 3 = 3[(2x + y – {5 – (x – 3y)}) + (7x – 4y + 3)]

Subtracted from 3x – 4y + 7.

Therefore, the required expression is (3x – 4y + 7) – 3[(2x + y – {5 – (x – 3y)}) + (7x – 4y + 3)]

(iii) The product of subtraction of x2– y2 + 4xy from 2x2 + y2 – 3xy is given by {(2x2 + y2 – 3xy) – (x2-y2 + 4xy)}

Above equation is added to 9x2 – 3y– xy,

{(2x2 + y2 – 3xy) – (x– y+ 4xy)} + (9x– 3y2– xy))

This is the required expression.

Exercise 7.4

Simplify each of the following algebraic expressions by removing grouping symbols.

Question 1: 2x + (5x – 3y)

Solution 1:

2x + (5x – 3y)

= 2x + 5x – 3y

On simplifying, we get

= 7x – 3y

Question 2: 3x – (y – 2x)

Solution 2:

3x – (y – 2x)

= 3x – y + 2x

On simplifying, we get

= 5x – y

Question 3: 5a – (3b – 2a + 4c)

Solution 3:

5a – (3b – 2a + 4c)

= 5a – 3b + 2a – 4c

On simplifying, we get

= 7a – 3b – 4c

Question 4: -2(x2 – y2 + xy) – 3(x2 +y2 – xy)

Solution 4:

– 2(x2 – y2 + xy) – 3(x2 +y2 – xy)

= -2x+ 2y2 – 2xy – 3x2 – 3y2 + 3xy

On rearranging,

= -2x2 – 3x2 + 2y2 – 3y– 2xy + 3xy

On simplifying, we get

= -5x– y2 + xy

Question 5: 3x + 2y – {x – (2y – 3)}

Solution 5:

3x + 2y – {x – (2y – 3)}

First, remove the parentheses. Then, we have to remove the braces.

Then we get expression as:

= 3x + 2y – {x – 2y + 3}

= 3x + 2y – x + 2y – 3

On simplifying, we get

= 2x + 4y – 3

Question 6: 5a – {3a – (2 – a) + 4}

Solution 6:

5a – {3a – (2 – a) + 4}

Firstly , remove the parentheses. Then, we have to remove the braces.

Then we get expression as:

= 5a – {3a – 2 + a + 4}

= 5a – 3a + 2 – a – 4

On simplifying, we get

= 5a – 4a – 2

= a – 2

Question 7: a – [b – {a – (b – 1) + 3a}]

Solution 7:

a – [b – {a – (b – 1) + 3a}]

Firstly, remove the parentheses, then the curly brackets, and then the square brackets.

Then we get the expression:

= a – [b – {a – (b – 1) + 3a}]

= a – [b – {a – b + 1 + 3a}]

= a – [b – {4a – b + 1}]

= a – [b – 4a + b – 1]

= a – [2b – 4a – 1]

On simplifying, we get

= a – 2b + 4a + 1

= 5a – 2b + 1

Question 8:  a – [2b – {3a – (2b – 3c)}]

Solution 8:

a – [2b – {3a – (2b – 3c)}]

Firstly, remove the parentheses, then the braces, and then the square brackets.

Then we get the expression:

= a – [2b – {3a – (2b – 3c)}]

= a – [2b – {3a – 2b + 3c}]

= a – [2b – 3a + 2b – 3c]

= a – [4b – 3a – 3c]

On simplifying we get,

= a – 4b + 3a + 3c

= 4a – 4b + 3c

Question 9: -x + [5y – {2x – (3y – 5x)}]

Solution 9:

-x + [5y – {2x – (3y – 5x)}]

Firstly remove the parentheses, then remove braces, and then the square brackets.

Then we get the ecpression:

= – x + [5y – {2x – (3y – 5x)}]

= – x + [5y – {2x – 3y + 5x)]

= – x + [5y – {7x – 3y}]

= – x + [5y – 7x + 3y]

= – x + [8y – 7x]

On simplifying we get

= – x + 8y – 7x

= – 8x + 8y

Question 10: 2a – [4b – {4a – 3(2a – b)}]

Solution 10:

2a – [4b – {4a – 3(2a – b)}]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= 2a – [4b – {4a – 3(2a – b)}]

= 2a – [4b – {4a – 6a + 3b}]

= 2a – [4b – {- 2a + 3b}]

= 2a – [4b + 2a – 3b]

= 2a – [b + 2a]

On simplifying, we get

= 2a – b – 2a

= – b

Question 11: -a – [a + {a + b – 2a – (a – 2b)} – b]

Solution 11:

-a – [a + {a + b – 2a – (a – 2b)} – b]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= – a – [a + {a + b – 2a – (a – 2b)} – b]

= – a – [a + {a + b – 2a – a + 2b} – b]

= – a – [a + {- 2a + 3b} – b]

= – a – [a – 2a + 3b – b]

= – a – [- a + 2b]

On simplifying, we get

= – a + a – 2b

= – 2b

Question 12: 2x – 3y – [3x – 2y -{x – z – (x – 2y)}]

Solution 12:

2x – 3y – [3x – 2y -{x – z – (x – 2y)}]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= 2x – 3y – [3x – 2y – {x – z – (x – 2y)})

= 2x – 3y – [3x – 2y – {x – z – x + 2y}]

= 2x – 3y – [3x – 2y – {- z + 2y}]

= 2x – 3y – [3x – 2y + z – 2y]

= 2x – 3y – [3x – 4y + z]

On simplifying, we get

= 2x – 3y – 3x + 4y – z

= – x + y – z

Question 13: 5 + [x – {2y – (6x + y – 4) + 2x} – {x – (y – 2)}]

Solution 13:

5 + [x – {2y – (6x + y – 4) + 2x} – {x – (y – 2)}]

Firstly remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= 5 + [x – {2y – (6x + y – 4) + 2x} – {x – (y – 2)}]

= 5 + [x – {2y – 6x – y + 4 + 2x} – {x – y + 2}]

= 5 + [x – {y – 4x + 4} – {x – y + 2}]

= 5 + [x – y + 4x – 4 – x + y – 2]

= 5 + [4x – 6]

= 5 + 4x – 6

= 4x – 1

Question 14: x– [3x + [2x – (x– 1)] + 2]

Solution 14:

x– [3x + [2x – (x– 1)] + 2]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= x2 – [3x + [2x – (x2 – 1)] + 2]

= x2 – [3x + [2x – x2 + 1] + 2]

= x2 – [3x + 2x – x2 + 1 + 2]

= x2 – [5x – x2 + 3]

On simplifying we get

= x2 – 5x + x2 – 3

= 2x2 – 5x – 3

Question 15: 20 – [5xy + 3[x2 – (xy – y) – (x – y)]]

Solution 15:

20 – [5xy + 3[x2 – (xy – y) – (x – y)]]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= 20 – [5xy + 3[x2 – (xy – y) – (x – y)]]

= 20 – [5xy + 3[x2 – xy + y – x + y]]

= 20 – [5xy + 3[x2 – xy + 2y – x]]

= 20 – [5xy + 3x2 – 3xy + 6y – 3x]

= 20 – [2xy + 3x2 + 6y – 3x]

On simplifying we get

= 20 – 2xy – 3x2 – 6y + 3x

= – 3x– 2xy – 6y + 3x + 20

Question 16: 85 – [12x – 7(8x – 3) – 2{10x – 5(2 – 4x)}]

Solution 16:

85 – [12x – 7(8x – 3) – 2{10x – 5(2 – 4x)}]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= 85 – [12x – 7(8x – 3) – 2{10x – 5(2 – 4x)}]

= 85 – [12x – 56x + 21 – 2{10x – 10 + 20x}]

= 85 – [12x – 56x + 21 – 2{30x – 10}]

= 85 – [12x – 56x + 21 – 60x + 20]

= 85 – [12x – 116x + 41]

= 85 – [- 104x + 41]

On simplifying, we get

= 85 + 104x – 41

= 44 + 104x

Question 17: xy [yz – zx – {yx – (3y – xz) – (xy – zy)}]

Solution 17:

Given xy [yz – zx – {yx – (3y – xz) – (xy – zy)}]

Firstly, remove the parentheses, then remove braces, and then the square brackets.

Then we get the expression:

= xy – [yz – zx – {yx – (3y – xz) – (xy – zy)}]

= xy – [yz – zx – {yx – 3y + xz – xy + zy}]

= xy – [yz – zx – {- 3y + xz + zy}]

= xy – [yz – zx + 3y – xz – zy]

= xy – [- zx + 3y – xz]

On simplifying, we get

= xy – [- 2zx + 3y]

= xy + 2xz – 3y